Analisis Kerentanan Website Desa Sekecamatan Bengkalis Menggunakan Vulnerability Assessment - Sani, Muhammad; Subandri, Muhammad Asep (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The village website is used as the main means of providing services and disseminating information to the community. However, without good security, these websites are vulnerable to cyber attacks. This research aims to analyze the level of vulnerability of village websites in Bengkalis District using the Vulnerability Assessment method. In this research, eight village websites were tested using the Nmap and OWASP ZAP tools to find security gaps. The test results show that there are several weaknesses with different risk levels, ranging from High, Medium, Low, to Informational. Some of the problems found include the use of vulnerable JavaScript libraries, inadequate security settings, and the risk of attacks such as Clickjacking and Cross-Site Scripting (XSS). To make websites safer, this research suggests several improvements, such as updating the security system, adding protection against attacks, and improving website security settings. With this research, it is hoped that village governments can better understand and improve the security of their websites so that they are better protected from cyber threats.